Genetic disorders of carbonic anhydrases II and IV - Sly, William (Henry Stewart Talks, 2007)
Carbonic anhydrase deficiencies, History of the disease, Roles of CA II and IV in disease, Sulfonamide inhibitors for treatment of some disorders, Characterization of CA isozymes, CA IV discovery and function, Mouse knockout models of CA deficiencies, CA IV, unfolded protein response and retinitis pigmentosa, ER stress and apoptosis in the choriocapillaris, Chemical chaperones and treatment of retinitis pigmentosa, Future studies
Archived at 2021/02/25